Synthesis, Characterization and Biological Activities of New 1-[(2, 5- Dichloroanilinomalonyl)-3-(N-2'-cyanoethyl)-2-(N-benzoyl)- 2,5-dichloroanilino)]-5-phenyl Pyrazoline Derivatives - Narayan Sharma, Raj; Sharma, K.P.; Dixit, S.N. (Asian Journal of Chemistry, 2010)
A series of new 1-[(2,5-dichloroanilinomalonyl)-3-(N-2'-cyanoethyl)-2-(N-benzoyl)2,5- dichloroanilino)]-5-phenyl pyrazoline have been synthesized in 44-76 % yield, by the reaction of N-cinnamoyl-N-2'-cyanoethyl-2,5-dichloroaniline with ethyl-2-[(N-benzoyl)-2,5- dichloroanilido]acetohydrazide. Pyrazolines are yellow, cream and brown colour solids, having high melting points. Identity of these products has been established by elemental analysis and spectral data. Newly synthesized compounds (6a-t) have been tested for their antibacterial activity against gram positive bacteria S. albus, S. aureus and gram negative bacteria E. coli and Pseudomonas poisonous. The compounds (6a, 6b, 6c, 6f, 6g, 6j, 6m and 6r) shown significant activity and the compounds (6i, 6k, 6l, 6p, 6t) have shown moderate activity. The same compounds were tested for their antifungal activity against Candida albicans, Aspergillus niger and Alternaria alternata at concentration of 30 mg/mL using sabouraud dextrose agar media. The compounds (6c, 6j, 6m and 6r) shown significant activities and compounds (6a, 6b, 6f and 6g) were found to be moderately active against Candida albicans and Aspergillus niger. All the other compounds did not show significant activity against the fungi at the concentration used. Some new compounds have been tested for antitubercular activity in vitro using Mycobacterium tuberculosis. The compounds were incorporated into Lowenstein Jensen egg medium having concentrations of 10 and 100 mg/mL and were inoculated with Mycobacterium tuberculosis, H27, Rv strains, incubated at 37 ºC and observed. The compounds (6a, 6b, 6c, 6f, 6g, 6j and 6m) inhibited the growth of Mycobacterium tuberculosis at 100 mg/mL concentration other compounds were found to be inactive.